A Study on the Livelihood Sources and Welfare Levels of Small-Scale Fishing Households in Tapanuli Tengah Regency, Sumatera Utara - Tirta Anugerah; Juliana Pebrina Siburian; Tika Nisari; Husnul Yaqin; Shofian Nanda Adiprayoga (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2024)
Indonesia is known as an “undersea paradise” because of its extraordinary wealth of marine biodiversity and fishery resources. With this nickname, coastal communities should have a decent life. However, in reality, their welfare is not in line with the wealth of marine resources, especially for fishermen. The lives of fishermen are often colored by economic challenges, weather uncertainty, and environmental changes that impact their welfare. This study aims to identify sources of livelihood, identify levels of welfare, and identify livelihood strategies carried out by fishing households. Through a survey that we conducted on 35 small-scale fishing households on the West Coast of North Sumatra, we found that most of them were still classified as less prosperous. Although the livelihood analysis shows that their sources of income are quite diverse, the contribution of income outside of fishing has not been able to improve their level of welfare. The results of this study also show that fishermen are not a passive group of people. Realizing the uncertainty in their livelihoods, they try to take advantage of existing opportunities by implementing livelihood strategies. The livelihood strategies carried out by fishermen are classified into economic dimensions, ecological dimensions, and social dimensions.